METHOD OF FPV DRONE STABILIZATION ON AN AUTOMATICALLY DETERMINED TARGET AND ITS FURTHER OBSERVATION (Computer systems and information technologies, 2025)
The paper considers the problem of the lack of stabilization in FPV drones, which significantly limits their functionality for applications that require precise tracking of a specific target. Such drones, although characterized by high maneuverability and affordable cost, are inferior to commercial quadcopters such as the DJI Mavic, which are equipped with effective stabilization systems, but are significantly more expensive due to the use of proprietary technologies. The paper proposes a new approach to stabilizing FPV drones, based on the use of computer vision algorithms for automatic target detection and tracking. The main concept includes target detection based on image analysis from the drone camera, further determination of its trajectory and transmission of appropriate control commands to the flight controller using the MAVLink protocol. This approach allows to significantly increase the accuracy and stability of FPV drones when performing tasks that require focusing on an object, such as infrastructure inspection, search and rescue operations, or video shooting. The proposed solution is based on accessible and open technologies, which ensures its adaptability and low implementation cost. The paper describes in detail the developed system architecture, which includes a computer vision module for video stream analysis, algorithms for data processing and filtering, as well as integration mechanisms with existing flight controllers. A series of experiments were conducted to evaluate the effectiveness of the proposed approach. The results demonstrate that the proposed system is able to ensure stable drone tracking on a specified target even in difficult flight conditions.
Keywords: stabilization; FPV drone; MAVLink protocol; automatic target detection